Competence, Rewards, and Geographic Proximity in Nutrition Practitioner Performance - Fauzie Rahman; Syamsul Arifin; Rosihan Adhani; Meitria Syahadatina Noor; Husaini Husaini; Muhammad Abdan Shadiqi; Neka Erlyani; Muhamad Muslim (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Based on data from the Indonesian Health Survey, the stunting rate in South Kalimantan Province in 2023 reached 24.7%. The target for reducing the national stunting rate in 2024 is 14%. Nutrition practitioner play a diverse and crucial role in handling stunting, from assessment and education to policy intervention and advocacy. This study aims to determine the effect of competence, appreciation and geographical proximity on the performance of nutrition practitioner with management span as a moderating variable in preventing stunting cases. Methods: This type of research is observational analytic with a cross-sectional design. The location of this research is at the Health Center in the working area of the South Kalimantan Provincial Health Office and the duration of the research is 2 months. The sample of this research is 280 respondents who were taken using the cluster sampling technique. The data collection method uses a questionnaire. Ethical approval was obtained from the Health Research Ethics Commission of the Faculty of Medicine and Health Sciences, Lambung Mangkurat University with number No.067/KEPK-FKIK ULM/EC/V/2024 and participants signed the Informed Consent. Results: The findings show that geographical proximity (t = 0.658, p = 0.510) has no significant effect on TPG performance, indicating that the distance between program targets and TPG members does not influence outcomes. In contrast, competence (t = 5.404, p = 0.000), rewards (t = 3.766, p = 0.000), and management range (t = 2.577, p = 0.010) have a significant positive impact on performance, where higher competence and more frequent rewards lead to improved results. The results further demonstrate that management range strengthens the effect of both rewards (t = 3.872, p = 0.000) and competence (t = 3.549, p = 0.000) on performance, indicating that effective coordination enhances their impact. However, the interaction between management range and geographical proximity (t = 0.742, p = 0.458) is not significant, suggesting that distance does not moderate the influence of management range on performance. Conclusion: Competence and reward is the factor influencing performance, while geographical proximity do not show significant influence. Competence, rewards, geographical proximity, and management span simultaneously influence performance with a contribution of 71% (R² = 0.710). This finding suggests the need for organizations to focus on improving TPG competencies through continuous training, skill development, and knowledge enhancement. In addition, it is important to explore other factors outside the research model that may have a significant impact on performance, including intrinsic motivation and better work system support.